The Design of Pixelated SIW Horn Antennas With Nearly Equal Beamwidths Using Binary Ink Stamp Optimization - Zechmeister, Jaroslav; Láčík, Jaroslav; Kadlec, Petr (IEEE, 2021)
In this paper, linearly and circularly polarized single-layer Substrate Integrated Waveguide (SIW) horn antennas with nearly equal half power beamwidths in principal planes for the 24 GHz ISM band are designed. The uniqueness of the solution lies in the application of a pixelated structure to the design of these SIW horn antennas. For the design, a novel heuristic algorithm called Binary Ink Stamp Optimization is proposed. At first, the ability of the proposed algorithm is proved over fifteen benchmark functions and compared with the results of six state-of-the-art optimization algorithms. Then, the novel algorithm is exploited for the design of the pixelated part of the antennas. The antennas are manufactured using low-cost 3D printing technology. The experimental results prove that the linearly polarized antenna has a reflection coefficient below 18 dB in the whole 24 GHz ISM band. At the center frequency of this band, the antenna gain is 14.2 dBi, and the level of side lobes is below 15 dB in E and H-planes. In addition, E and H-plane half power beamwidths are 26.5° and 25°, respectively. The circularly polarized antenna radiates a right-hand circularly polarized (RHCP) wave, the reflection coefficient, and axial ratio are below 12 dB and 3 dB in the whole 24 GHz ISM band, respectively. At the center frequency of this band, the antenna gain is 8.9 dBi and the level of side lobes is below 7.4 dB in both principal planes. Further, the half power beamwidths in principal planes are 30.6° and 33.4°, respectively.

In this paper, linearly and circularly polarized single-layer Substrate Integrated Waveguide (SIW) horn antennas with nearly equal half power beamwidths in principal planes for the 24 GHz ISM band are designed. The uniqueness of the solution lies in the application of a pixelated structure to the design of these SIW horn antennas. For the design, a novel heuristic algorithm called Binary Ink Stamp Optimization is proposed. At first, the ability of the proposed algorithm is proved over fifteen benchmark functions and compared with the results of six state-of-the-art optimization algorithms. Then, the novel algorithm is exploited for the design of the pixelated part of the antennas. The antennas are manufactured using low-cost 3D printing technology. The experimental results prove that the linearly polarized antenna has a reflection coefficient below 18 dB in the whole 24 GHz ISM band. At the center frequency of this band, the antenna gain is 14.2 dBi, and the level of side lobes is below 15 dB in E and H-planes. In addition, E and H-plane half power beamwidths are 26.5° and 25°, respectively. The circularly polarized antenna radiates a right-hand circularly polarized (RHCP) wave, the reflection coefficient, and axial ratio are below 12 dB and 3 dB in the whole 24 GHz ISM band, respectively. At the center frequency of this band, the antenna gain is 8.9 dBi and the level of side lobes is below 7.4 dB in both principal planes. Further, the half power beamwidths in principal planes are 30.6° and 33.4°, respectively.
The Design of Pixelated SIW Horn Antennas With Nearly Equal Beamwidths Using Binary Ink Stamp Optimization
Keywords: Substrate integrated waveguide (SIW); SIW horn antenna; pixelated antenna; discrete evolutionary algorithm; binary optimization; Substrate integrated waveguide (SIW); SIW horn antenna; pixelated antenna; discrete evolutionary algorithm; binary optimization